"@Government There's a pothole in my street!": Canadian citizens' adoption choices of social media use in citizen‐government relations. (20th November 2021) - Homburg, Vincent; Moody, Rebecca
Abstract: Social media platforms such as Twitter and Facebook offer new opportunities for co‐production and interaction between citizens and government agencies. Until now, explanations of why citizens use social media to interact with government have been lacking in the literature. This article concludes on the basis of survey data gathered among Canadian citizens that social media use in citizen‐government relations is explained by citizens' perceived effectiveness and trust in social media organizational infrastructure, with trust in government, social media anxiety and ease of use not having an impact. Implications for research and practice are discussed. Sommaire: Les plateformes de médias sociaux comme Twitter et Facebook offrent de nouvelles opportunités de coproduction et d'interaction entre les citoyens et les organismes gouvernementaux. Jusqu'à présent, la littérature manquait d'expliquer les raisons pour lesquelles les citoyens utilisent les médias sociaux pour interagir avec le gouvernement. Cet article présente des données de sondage recueillies auprès de citoyens canadiens; elles attestent que l'utilisation des médias sociaux dans les relations entre citoyens et gouvernement s'explique par la perception des citoyens de l'efficacité et de la confiance dans l'infrastructure organisationnelle des réseaux sociaux, alors que la confiance accordée au gouvernement, l'anxiété et la convivialité des médias sociaux n'ont aucune incidence. Nous discutons ensuite des implications pour la recherche et la pratique.